Colonial Niger Delta and Intra-Regional Conflict in Selected Nigerian Plays - Gomba, Obari (Acta Universitatis Danubius. Communicatio, 2022)
This research examines and analyses the depiction of intra-regional conflicts in selected historical plays that are set in the colonial era of Nigeria’s resource-rich Niger Delta region. The plays are Miesoinuma Minima’s King Jaja or the Tragedy of a Nationalist and Odum Egege, Ola Rotimi’s Ovonramwen Nogbaisi, and Ahmed Yerima’s The Trials of Oba Ovonramwen. The plays depict two regional centres of power and their extensive control. Rather than situate the texts in the context of Nigeria’s pre-Independence nationalism against British rule, attention is given to intra-regional otherness and its resultant conflict.